Analysis of Dr. Aisah Dahlan's Lecture " Communication Tips" Comfortable in Family ” On YouTube SUAS Videos( Practice Interpersonal Communication and Gender in Islamic Marriage ) - Sofa Aulia Fauziah (Journal of Islamic Family Law, 2026)
This study aims to analyze how interpersonal communication in Muslim families is influenced by gender, emotional intelligence, and Islamic values. The primary focus of the study is on the communication relationships within families between husband and wife and parents and children through a neuroscience approach and interpersonal communication theory, as explained in Dr. Aisah Dahlan's lecture entitled "Tips for Comfortable Communication in the Family." This study also seeks to explain how biological and psychological differences between men and women impact the roles and communication patterns in Islamic households. This is a qualitative study using content analysis methods on video lectures by Dr. Aisah Dahlan, CMHt., CM., NLP on the SUAS Videos YouTube channel. The focus is on analyzing media message content systematically, objectively, and measurably to identify specific patterns, meanings, themes, categories, or frequencies within a medium. Data were analyzed through observation, thematic classification, and interpretation based on interpersonal communication theory (DeVito, 2016), emotional intelligence theory (Goleman, 1995), and Islamic communication values such as ta'aruf (relationship), sabr (compassion), rahmah (mercy), and tasamuh (compassion). This study also integrated neuroscience research findings on differences in the male and female brains to enrich our understanding of gender-based communication within families. The study shows that interpersonal communication in Muslim families is strongly influenced by emotional intelligence and gender differences rooted in biological and psychological aspects. Women are predominantly verbal and expressive, while men are more oriented toward logic and action. These differences often lead to misunderstandings if not understood empathetically. Dr. Aisah Dahlan's lecture emphasized the importance of recognizing a partner's "love language" to build balanced communication between logic and emotion. The analysis also found that Islamic values such as sabr (patience), rahmah (compassion), and muhasabah (self-awareness) reinforce the concept of emotional intelligence within the family context. This research provides a conceptual contribution to the development of Islamic and gender-based interpersonal communication studies. Practically, the results can serve as a guide for Muslim couples to maintain harmony by building empathetic, spiritually grounded communication. Understanding biological, psychological, and innate gender differences is key to creating a harmonious, morally and emotionally equal household.